Natural regeneration and carbon budget of rock dumpsite of an ex-mine site in Jose Panganiban, Camarines Norte, Philippines - Abanto, Rusty G.; Florece, Leonardo M. (2011)
Regeneration of mined-out area is possible, through poses herculean challenges because of technical and financial constraints. This study assessed the natural regeneration in the rock dump site of abandoned mining area in Larap, Jose Panganiban, Camarines Norte, Philippines and was premised on the hypothesis that natural regeneration of mined-out areas can significantly contribute to rehabilitation and carbon sequestration. Field measurement of natural regeneration were conducted using quadrat method and identified eight species belonging to eight genera and seven families. Diversity indices yielded no significant difference using t-test. Carbon sequestration analysis showed that natural regeneration has 2.78 t ha-1 C stored in the biomass and 22.55 t ha-1 of C sequestration in the soil through soil organic carbon. Natural regeneration indicates that regreening the mined soil is possible if natural process of ecological succession is allowed. When properly managed and protected, natural regeneration offers enormous opportunity not only in sequestering but also in increasing productivity of the area. This study recommends the determination of carbon pools below the ground biomass (roots); exploring other sampling techniques that could capture the best picture of the whole grassland ecosytem; and strictly enforce the policy in final mine rehabilitation program before cessation of mining operation to avoid mined-out areas being left out by mining projects.
Keywords: Carbon dioxide sequestration